Political Communication of Lakpesdam NU of Greater Malang in Strengthening Political Awareness and Local Democracy - Aminulloh, Akhirul; Ananda, Kun Sila; Fattah, Zulfikar Waliyuddin; Nanda Harda Pratama Meiji,; Ronny Ersya Novianto Putra, (Mediakita, 2026)
This study aims to analyze the political communication strategies of community institutions to strengthen political awareness and build participatory democracy at the local level. The focus of the study was directed at the three branches of the Institute for Human Resources Studies and Development of Nahdlatul Ulama in Malang Raya. The research uses a qualitative case-study approach. The data collection was conducted through in-depth interviews with the management of Lakpesdam NU in Malang City, Malang Regency, and Batu City. The data analysis in this study follows the interactive model of Miles and Huberman, which comprises three main stages: data reduction, data presentation, and conclusion. The results of the study show that there is a dialectic of three main approaches in Lakpesdam NU’s political communication strategy: structural, cultural, and critical. Lakpesdam NU of Malang City focuses more on structural paths, including building political awareness of cadres through education, conducting policy advocacy, and strengthening the role of civil society. Meanwhile, Lakpesdam NU of Malang Regency and Batu City tend to prioritize a cultural approach, namely conveying political messages through religious symbols, the character and moral authority of the kiai, and appreciation of local values that live in the community. All three also employ a reflective-critical approach to counter apathy, political pragmatism, and symbolic participation. The communication model implemented by the Lakpesdam NU can serve as a reference for strengthening local democracy rooted in religious communities in Indonesia. This research contributes to enhancing political communication rooted in cultural-religious values through a dialectical model that integrates structural, cultural, and critical approaches.